Values and validity of fetal parameters by ultrasound and Doppler as markers of fetal lung maturity - Radwa A. Kandil; Al shymaa Z. El shahawy; Mohamed H. El Shafiey; Reda A. Alarabawy (The Egyptian Journal of Radiology and Nuclear Medicine, 2021)
Abstract Background In this study, we combined ultrasound and Doppler parameters to conclude the most accurate and applicable method for fetal lung maturity assessment. The purpose is to reduce risk of neonatal respiratory distress by assessment of fetal lung maturity through ultrasound and Doppler instead of amniocentesis. Results A total of 120 women were included. The ultrasound examination was performed at a gestational age ranging between 30 and 37 weeks and delivery occurred within 72 h from ultrasound. After birth, 19 fetuses were diagnosed with RDS. The ultrasound parameters assessed for fetal lung maturity showed varying sensitivity and specificity but presence of proximal tibial epiphyses showed the highest sensitivity (91%) and specificity (95%) followed by the presence of distal femoral epiphyses with 90% sensitivity and 84% specificity. The placental grade III maturity showed a sensitivity of 81% and 74% specificity followed by the presence of the amniotic fluid free-floating particles with an 83% sensitivity and 63% specificity, while echogenic fetal thalamus showed 77% and 79% for sensitivity and specificity, respectively, for prediction of fetal lung maturity. By using the fetal biometry, we could report that a BPD between 82.8 and 93.5 mm, AC between 295 and 322 mm, and FL (62.7-72.1 mm) correlated with mature fetal lungs. Regarding Doppler indices, increased resistive index of umbilical artery > 0.69 and of pulmonary artery > 0.78 correlated with neonatal RDS while fetuses with UtA RI values between 0.43 and 0.66 noticed in RDS vs (0.42-0.57) in the non-RDS. MCA RI values are also higher in RDS 0.77–0.88 vs 0.74–0.79 in non-RDS. On the other hand, analysis of colon grading and fetal lung echogenicity in relation to liver showed no significant value in the assessment of fetal lung maturity. Conclusion Ultrasound and Doppler showed good predictive value and accuracy and is considered a valuable non-invasive procedure in assessment of fetal lung maturity. However, no single parameter alone could show a definitive sign